Scientific content analysis of Light Emitting Diode (LED) for high school physics STEM based learning - Andrilana Andrilana; Ishafit Ishafit; Dian Artha Kusumaningtyas (AL-TARBIYAH: Jurnal Pendidikan (The Educational Journal), 2024)
The embedded STEM approach is currently the most easily implemented in Indonesia compared to other types of approaches. This approach requires a context to be delivered in the learning process. The context selection must consider its relevance to everyday life and be closely linked to process competencies. This study conducts a scientific content analysis of Light Emitting Diode. It investigates its potential application in high school physics embedded-STEM learning. The research adopts a descriptive qualitative methodology using the Model of Educational Reconstruction as the research framework. Data were collected through a literature review of three scientific references on LEDs. The scientific content analysis of LEDs was performed using the hermeneutic analysis method. The literature analysis of these subthemes revealed that the significant Physics concepts relevant to LEDs include energy and its transformations, direct current electricity, electromagnetic radiation, electronic systems, and quantum physics. Consequently, LEDs hold significant potential as a context for embedded STEM learning in high school physics. The results of this study provide a foundation for the subsequent phase of constructing embedded STEM learning designs with the topic of LEDs, such as the development of textbooks, learning strategies, and their evaluation.Keywords: contextual physics, LED, embedded STEM